How can blended learning English-as-a-second-language courses incorporate with cultural heritage, building, and sense of sustainable development goals?: A case study - Kwee, Ching Ting Tany; Dos Santos, Luis Miguel (Frontiers in Education, 2022)
This study aims to study how the incorporation of digitised heritage buildings into blended English as a second language teaching can facilitate students’ attainment of the Sustainable Development Goals target of quality education, specifically increasing cultural awareness and consciousness of global citizenship. Based on the lens of social cognitive theory and case study approach, the researchers collected qualitative data from 40 participants who enrolled in a blended English-as-a-Second Language course in a community college in the United States. The results indicated that cultural heritage and buildings in my blended language learning curriculum, expand the knowledge to other subject matter, and beyond the book were the three main themes. Based on the current course and curriculum designs with the elements of cultural heritage, buildings, and senses of Sustainable Development Goals, students expressed positive experiences in the fields of second language acquisition, employments of the computer-aided and technologically-assisted tools, and interdisciplinary knowledge. University leaders, department heads, curriculum developers, instructors, and trainers should use this study as the reference to reform and upgrade their current materials with cultural heritage, buildings, and senses of Sustainable Development Goals in order to offer the comprehensive training to college and university students.